To create a true equivalent system, you can manipulate the existing equations in the system.
The given equations for System A are:
- \(-x + y = 1\)
- \(x + y = 11\)
We want to find an equation that is equivalent to these.
Let's analyze the provided options:
-
\(2x + 2y = 12\):
- If we divide the original equation \(x + y = 11\) by 1, we find \(2(x + y) = 2(11)\), which gives us \(2x + 2y = 22\), so this does not match with \(2x + 2y = 12\).
-
\(-x - y = -1\):
- If we take the first equation \(-x + y = 1\) and multiply both sides by -1, we get \(-x - y = -1\). This means this is an equivalent equation.
-
\(2y = 12\):
- This would imply \(y = 6\), which doesn't match our systems' equations.
-
\(-2x - 2y = -22\):
- This is just multiplying the equation \(x + y = 11\) by -2, which gives us \(-2(x+y) = -2(11)\) thus resulting in \(-2x - 2y = -22\), but it would not be an option since it does not match what we already have.
Thus, the only choice that creates a true equivalent system is \(-x - y = -1\).